Urinary Metabolic Profile of Patients with Transfusion-Dependent β-Thalassemia Major Undergoing Deferasirox Therapy - Giovanna Capolongo; Miriam Zacchia; Amerigo Beneduci; Silvia Costantini; Patrizia Cinque; Anna Spasiano; Giuseppina De Luca; Maria Enrica Di Pietro; Paolo Ricchi; Francesco Trepiccione; Giovambattista Capasso; Aldo Filosa (Karger Publishers, 2020)
Introduction: Renal dysfunction is a frequent complication in patients suffering from β-thalassemia major (β-TM). The aim of this study was to analyze the renal function and urine metabolomic profile of β-TM patients undergoing transfusions and deferasirox (DFX) therapy, in order to better characterize and shed light on the pathogenesis of renal disease in this setting. Methods and Subjects: 40 patients affected by β-TM treated with DFX and 35 age- and gender-matched healthy controls were enrolled in the study. Renal function was assessed. Glomerular filtration rate (GFR) was estimated with CKD-EPI and Schwartz formula for adults and children, respectively. Renal tubular function and maximal urine concentration ability were tested. Urine specimens were analyzed by nuclear magnetic resonance spectroscopy to identify the urinary metabolite profiles. Results: The study of renal function in β-TM patients revealed normal estimated (e)GFR mean values and the albumin-to-creatinine ratio was <30 mg/g. The analysis of tubular function showed normal basal plasma electrolyte levels; 60% of patients presented hypercalciuria and many subjects showed defective urine concentration. Several amino acids, N-methyl compounds, and organic acids were overexcreted in the urine of thalassemic patients compared with controls. Discussion: The major finding of this work is that β-TM patients and controls exhibit different concentrations of some metabolites in the urine. Early recognition of urinary abnormalities may be useful to detect and prevent kidney damage.